(untitled) (Journal of the College of Basic Education, 2026)
Within the framework of employing modern teaching strategies aimed at fostering a close link between art education and contemporary concepts, the present study addresses the following central question: What is the effect of the Wilen and Phillips strategy on developing analytical thinking among students at the Institute of Fine Arts in the subject of Art Analysis and Criticism? The current research aims to determine the impact of the Wilen and Phillips strategy on enhancing analytical thinking skills among students at the Institute of Fine Arts within the context of the Art Analysis and Criticism curriculum. The researcher arrived at the following findings: The study contributed to the enhancement of analytical thinking among students at the Institute of Fine Arts (specifically, the experimental group). A statistically significant cognitive development in analytical thinking was observed following the implementation of the strategy; this confirms the efficacy of the Wilen and Phillips strategy in fostering this specific mode of thinking among the students.